Measuring the Impact of the COVID-19 Shutdown on Great Lakes Water Quality Using Remote Sensing - Bosse, Karl R.; Sayers, Michael J.; Shuchman, Robert A.; Lekki, John; Tokars, Roger (Frontiers in Marine Science, 2021)
The states of Michigan and Ohio issued shutdown orders in mid-March 2020 in an attempt to slow the spread of the coronavirus (COVID-19), resulting in widespread disruption to economic and human activity. This study, which was commissioned by NASA headquarters, utilized satellite remote sensing data from the Visible Infrared Imaging Radiometer Suite sensor onboard the Suomi National Polar-orbiting Partnership satellite to investigate whether these changes in activity led to any short-term changes in water quality in the Great Lakes region by comparing 2020 data to a historic baseline. The water quality parameters examined included chlorophyll-a (CHL) and total suspended solids (TSS) concentrations, water clarity, and harmful algal bloom (HAB) extent. These parameters were investigated in two Great Lakes basins which experience significant anthropogenic pressure: the western basin of Lake Erie (WBLE) and Saginaw Bay in Lake Huron (SBLH). TSS concentrations in April 2020 were below the historic baseline in both basins, and largely remained low until September. SBLH also experienced elevated CHL concentrations in April which persisted through the summer. Additionally, the WBLE HAB extent was down in 2020 after an early end to the growing season. However, this investigation found that the COVID-19 shutdowns were likely not a direct driver of these short-term anomalies. Instead, recent trends in the indicators and co-occurring anomalies in hydrological and meteorological conditions (e.g., lake temperature, river discharge, and wind speed) appeared to be more responsible for the detected water quality changes. Future work will investigate whether the shutdowns have a long-term or delayed impact on Great Lakes water quality.